Challenges and Adaptations Pre-Service Efl Teachers’ Perceptions on Implementing The Merdeka Curriculum In Teaching English - Hanum, Latifah; Dalimunte, Ahmad Amin (Jayapangus Press, 2025)
This study examines the challenges and adaptations encountered by pre-service English as a Foreign Language (EFL) teachers in implementing the Merdeka Curriculum. A qualitative case study approach was used to collect data from 89 final-year english education students at the state islamic university of north Sumatra who had completed teaching internships. The aim of the study was to explore the difficulties faced by these pre-service teachers in applying the new curriculum and the adaptation strategies they used to overcome them. The findings indicate that, although the pre-service teachers demonstrated a strong understanding of the curriculum's principles especially in integrating the Pancasila Student Profile into their teaching they faced significant challenges. These challenges included difficulties in designing lesson plans, implementing student-centered teaching methods, and conducting authentic assessments. Support from schools, including adequate facilities, guidance from senior teachers, and professional development, was crucial in helping them address these challenges. Additionally, adaptation strategies such as attending workshops, collaborating with peers, and independently seeking additional resources proved effective in enhancing their capacity to implement the curriculum. This study emphasizes the importance of ongoing collaboration among educational institutions, schools, and pre-service teachers. Continuous training, mentoring, and resource support are essential to ensure the successful implementation of the Merdeka Curriculum and better prepare future educators for curriculum innovations.